Phonon thermal transport in polycrystalline graphene:Effects of grain, vacancy and strain. (1st August 2023) - Yang, Ziqiang; Wang, Ruipeng; Li, Haipeng; Tang, Ho-Kin; Han, Kui
Highlights: Phonon thermal transport properties in polycrystalline graphene are studied. Grain size and grain orientation play important role in the phonon thermal conductivity of polycrystalline graphene. The introduction of strain and vacancy defects can decrease the phonon thermal conductivity of polycrystalline graphene. Abstract: The phonon thermal conductivity of polycrystalline graphene nanoribbons has been calculated by non-equilibrium molecular dynamics method. The effects of grain size and boundary orientation, vacancy defect and strain on the phonon thermal conductivity of polycrystalline graphene nanoribbons have been studied. It was found that for polycrystalline graphene nanoribbons with the same average grain size, the phonon thermal conductivity increased with the increase of nanoribbon length. At the same size of nanoribbons, the phonon thermal conductivity increases with the increase of grain size in polycrystalline graphene nanoribbons. Grain boundary orientation has also an important impact on the phonon thermal conductivity. In addition, the phonon thermal conductivity of polycrystalline graphene decreases with the increase of tensile strain/compressive strain because the strain induces the change of structure and mechanical properties, which affects the phonon transport behavior. Compared with the pristine graphene, the vacancy defects lead to the suppression of some phonon modes of polycrystalline graphene and thus the reduction of phonon thermal conductivity due to the enhancement of phonon boundary scattering and phonon defect scattering. Our results are helpful to understand the physical mechanism of phonon thermal transport in polycrystalline graphene, and provides an important guidance for the regulation of phonon thermal conductivity of polycrystalline graphene. Graphical abstract: The effects of grain boundary, vacansy defect and strain on phonon thermal conductivity of polycrystalline graphene nanoribbons are studied theoretically. Image, graphical abstract